Establishing bioclimatic design tools and strategies from southern Mindanao climate and vernacular architecture bioclimatic design in General Santos City's Gulf View Resort Community Complex - Orendain, Dan Jezreel A. (2010)
Green architecture, although it may be the hype and trend in the design world today, is still a foreign and unchartered area in the country's architecture scene. One of the main deterrents is the purported high initial cost compared to conventional construction and design. Green architecture is often thought of as buildings covered with solar panels, high-sensitivity glass windows and the like which are often not locally produced in the country. Importing them also is also out of the question as that consumes fossil fuels. Hence, the project, which was a resort community complex in General Santos City have to be designed in a way that initial costs would be not far from typical construction cost. Most community or resort developments within Mindanao fail to incorporate sustainable design in the planning and designing. The cost of developing green communities is easily perceived as more expensive than conventional developments. It is the aim of the research to develop a sustainable community by avoiding the proposal of high technology solutions. These solutions are not entirely discouraged because then may be added later if these technologies become more budget-friendly. This was done through the use of bioclimatic tools and strategies by contextualizing the said tools in Southern Mindanao. Bioclimatic design basically utilizes the sun, wind and the vernacular form, among many others, in the design of architecture. In theory, it will not bear additional cost to the construction since it only utilizes proper orientation of the building, the sizing of building elements and the proper use and orientation of greeneries to name a few. The research focus on three areas of study ? sun and light, wind, and form and envelope. Through interviews, photo documentations, comparisons, and actual computations of the weather data obtained; a set of flexible bioclimatic design strategies and guidelines were derived and established. These guidelines are rhetoretically applicable to the Southern Mindanao climate and topography. To evaluate the application of the design , these set of guidelines where then applied to the Gulf View Resort Complex which includes a resort complex, a residential area, a commercial strip and a barangay zone. Forms were derived by looking at common elements within the city-ships, waves, the fish, ripples and the like. Not all of the bioclimatic guidelines from the study were used but only those applicable to the climate of General Santos City. The vernacular architecture were also a form inspiration although it was used subtly to avoid direct references and possible bastadization of traditional motifs and forms which is a common mistake when appropriating indigenous architecture and design. It is good to note that the objectives of the study were met. Bioclimatic guidelines that are contextualized in the Southern Mindanao region were established. The processed itself can also be utilized by other designers working in a different region in order to derive the region's unique bioclimatic guidelines. Upon the application of the design to the buildings, these guidelines, along with other design considerations and standards, and the choices of aesthetics by the designers, produced a set of unique and distinct, yet are easy to familiarize with buildings. The buildings fortunately avoided looking too high tech and modern that usually alienates user, but rather produced a fresh outtake on what General Santos City structures can look like. These guidelines can also be utilized by students of architecture so that regional sustainable design may be incorporated to their thinking at an early stage. It is then a recommendation by the researcher that further detailed study be done in the climate of General Santos City. It is also good to note that there should be available climate data in outlaying municipalities and towns of General Santos City